To find \( \log_2(16 \cdot 64) \) using the rule \( \log_b(xy) = \log_b x + \log_b y \), we can express it as follows:
\[ \log_2(16 \cdot 64) = \log_2(16) + \log_2(64) \]
Now, we can calculate \( \log_2(16) \) and \( \log_2(64) \):
-
\( 16 \) can be expressed as \( 2^4 \), so: \[ \log_2(16) = \log_2(2^4) = 4 \]
-
\( 64 \) can be expressed as \( 2^6 \), so: \[ \log_2(64) = \log_2(2^6) = 6 \]
Now, we can substitute these values back into our equation:
\[ \log_2(16 \cdot 64) = \log_2(16) + \log_2(64) = 4 + 6 = 10 \]
Thus, the final result is:
\[ \log_2(16 \cdot 64) = 10 \]